Letramento multimodal e argumentação: analise de estratégias persuasivas no anuncio publicitário - Vieira, Mauriceia Silva de Paula (2017)
This article analyzes commercials aired on YouTube, in order to understand how different semiotic resources contribute to the ad might mean more and reach the target audience. Three video advertisements were selected in order to analyze their present resources, based on the Grammar Theory of Visual Design, one of the ramifications of social semiotics. Descriptive and qualitative analyses show that compositional, interactive and representational functions are articulated in the genre advertising and that the meanings constructed from the integration of the various semiosis are linked to the patterns of experience and social interactions according to each culture.